Fostering Critical Thinking in Biology Education Through a TGT-Based Digital Interactive Module - Fadillah, Neska; Adlini, Miza Nina (Universitas Negeri Semarang, 2025)
The advancement of 21st century education demands learning media that not only deliver subject content but also develop students’ critical thinking skills through interactive and collaborative experiences. This study aims to develop a digital interactive module based on the Team Games Tournament (TGT) model for the excretory system topic to enhance students’ critical thinking. The research employed the 4D development model, which includes the stages of Define, Design, Develop, and Disseminate. The Define stage involved a needs analysis through interviews, questionnaires, and curriculum reviews. In the Design stage, the module was created by integrating interactive elements such as videos, animations, quizzes, and problem-solving tasks based on the TGT framework. The Develop stage included expert validations and limited trials with 30 tenth-grade students, using instruments such as validation sheets, response questionnaires, and critical thinking tests based on Facione’s indicators. Validation results showed that the module was highly valid, with scores of 98.67% from media experts and 99% from subject experts. The practicality score was also high, with 97.23% from teachers and 90.67% from students. The module’s effectiveness was demonstrated by a significant increase in students’ critical thinking, with an average N-Gain score of 0.83 (high category). These findings indicate that the TGT-based digital interactive module is valid, practical, and effective, and it can serve as an innovative learning resource for improving students’ critical thinking in biology education.